SSR analysis for fruit and quality characters in infra-specific mapping population of melon - SINGH, SMITA; PANDEY, SUDHAKAR; RAGHUWANSHI, RICHA; PANDEY, VIKRAM; SINGH, MAJOR (The Indian Journal of Agricultural Sciences, 2015)
Melon has variations in fruit trait that play an important role in consumer acceptance and breeding programms. These traits are controlled by single or multiple genes. Keeping this in view a mapping population (F2:3) was developed between muskmelon (Cucumis melo var. Kashi Madhu) and snapmelon (Cucumis melo var. momordica accession B-159) having contrasting fruit traits. SSR (simple sequence repeat) markers selected from melon database were applied in F2 population. Linkage analysis was performed using Mapmaker/Exp.3.0, multi point ordering at LOD = 3.0, to find possible allelic interactions between the loci and fruit traits. The result showed five QTLs for fruit characters, viz. fruit length, fruit weight, number of fruits per plant and ascorbic acid content was found to be significantly linked with markers CSWCT22A, CMMS1-7, CMCTN-86, CMBR-170b, CMBR-70, CMCT134b, CMBR73, CMGT-108, CMMS30-3 at marker interval from 56.5 cM to 153.3 cM with phenotypic variance of 5.9 to 69%, respectively. The study could be useful for the comparative genetics and increases utility of SSR markers across different populations and environment particularly Indian melons.